2018
DOI: 10.3390/ma11050668
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Influence of Hydrostatic Pressure and Temperature on Nonlinear Optical Properties of GaAs/Ga0.7Al0.3As Morse Quantum Well in the Presence of an Applied Magnetic Field

Abstract: Studies aimed at understanding the nonlinear optical (NLO) properties of GaAs/Ga0.7Al0.3As morse quantum well (QW) have focused on the intersubband optical absorption coefficients (OACs) and refractive index changes (RICs). These studies have taken two complimentary approaches: (1) The compact-density-matrix approach and iterative method have been used to obtain the expressions of OACs and RICs in morse QW. (2) Finite difference techniques have been used to obtain energy eigenvalues and their corresponding eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…In the second study, by changing the concentration of the sample with different weight percentages, the nonlinear behavior of the synthesized nanoparticles by different methods was investigated. The nonlinear properties of T iN prepared by the Ball mill (350rpm), Ball mill (500rpm)co-precipitation, and sol-gel methods in different intensities and concentrations are shown in Figures 10,11,12,and 13. The results show well the change in the nonlinear behavior of T iN nanoparticles by changing the concentration, laser beam intensity and synthesis of nanoparticles.…”
Section: Nonlinear Optics Studiesmentioning
confidence: 76%
See 1 more Smart Citation
“…In the second study, by changing the concentration of the sample with different weight percentages, the nonlinear behavior of the synthesized nanoparticles by different methods was investigated. The nonlinear properties of T iN prepared by the Ball mill (350rpm), Ball mill (500rpm)co-precipitation, and sol-gel methods in different intensities and concentrations are shown in Figures 10,11,12,and 13. The results show well the change in the nonlinear behavior of T iN nanoparticles by changing the concentration, laser beam intensity and synthesis of nanoparticles.…”
Section: Nonlinear Optics Studiesmentioning
confidence: 76%
“…In fact, with this achievement, a change of the optical parameters is possible, which is an interesting fundamental scientific tool that leads to many advances in technologies related to optics and lasers [5][6][7][8]. Due to the great interest of researchers in this area, the research in the nonlinear optics field has grown significantly [1][2][3][4][9][10][11]. One way to achieve this goal is to make materials with different synthesis methods [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…We have to stress that the agreement between the results obtained via the two methods was perfect. Then, the first-order linear, third-order nonlinear, and total absorption coefficients (ACs) for the transitions between the ground and first excited states of electron confined within DMQW by following the standard density matrix formalism combined with the perturbation expansion method are obtained, respectively, as follows [9], [19], [20], [21], [31], [32], [33], [34]βfalse(1false)false(Epfalse)badbreakafter=Epħ0.2emμ0εR0.2emfalse|M12false|20.2emσv0.2emnormalΩ12false(E12badbreakafter−Epfalse)2badbreakafter+normalΩ1220.2em,βfalse(3false)false(Ep,Ifalse)badbreakafter=badbreakafter−0.2em20.2emI0.2emβfalse(1false)false(Epfalse)ε00.2emn…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These models provide a useful approximation for the potential energy of a diatomic molecule. Nonlinear optical properties of semiconductor QWs mainly depend on the asymmetry of the confinement potential and so the optical properties of the low dimensional semiconductor heterostructures with the Morse potential, due to the inherent asymmetric character, have been studied intensively [19], [20], [21], [22]. However, as far as we know, any study has not been reported on the optical properties of double Morse potential quantum wells in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the ILF on the electronic structure in a Gaussian quantum well were investigated by Sari et al [ 19 ]; Kasapoglu et al investigated the effects of non-resonant high-frequency ILF on the electronic and optical properties of both the symmetric and asymmetric double Morse quantum wells, and quantum wells/quantum dots which have Razavy potential [ 20 , 21 ]. Furthermore, some of these potentials, which are called QES, have been studied under electric and magnetic fields [ 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%